1999
DOI: 10.1080/135475099230967
|View full text |Cite
|
Sign up to set email alerts
|

8 Hydroxydeoxyguanosine as a biomarker of workplace exposures

Abstract: To date, the 8-hydroxydeoxyguanosine (8OHdG) DNA adduct has been used as a biomarker in 11 occupational health studies examining the potential for ten different workplace exposures to cause oxidative DNA damage. Exposures examined include asbestos, azo-dyes, benzene, chromium, coal dust, glassworks, rubber manufacturing, styrene, toluene and environmental tobacco smoke (ETS). Experimental designs that applied 8OHdG as biomarker varied dramatically among the studies. For example, one study detected increased ur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 68 publications
0
24
1
Order By: Relevance
“…One study even reported an insignificant negative association between smoking and urinary 8-OHdG levels (Nilsson et al 2004). Many occupational studies did not find higher concentrations of 8-OHdG in smokers even though smoking has consistently been recognized to be a cofounder for 8-OHdG (Angerer et al 2007;Pilger and Rüdiger 2006;Toraason 1999). Regardless, smoking is a factor that should not be ignored.…”
Section: Discussionmentioning
confidence: 83%
“…One study even reported an insignificant negative association between smoking and urinary 8-OHdG levels (Nilsson et al 2004). Many occupational studies did not find higher concentrations of 8-OHdG in smokers even though smoking has consistently been recognized to be a cofounder for 8-OHdG (Angerer et al 2007;Pilger and Rüdiger 2006;Toraason 1999). Regardless, smoking is a factor that should not be ignored.…”
Section: Discussionmentioning
confidence: 83%
“…Higher levels of 8-oxo-dG have been detected in a central site in the lungs of cigarette smokers, and a positive association between 8-oxo-dG levels in lung tissue and the Brinkman index (cigarettes/day  years) obtained from smokers and exsmokers has been reported [63]. Also, lymphocytes have been used as a surrogate tissue to detect 8-oxo-dG from smokers and nonsmokers [25,64]. Consistent with the above observations, we detected signi®cantly higher levels of 8-oxo-dG in lymphocyte DNA of lung cancer cases than of corresponding controls, who were predominantly current smokers ( Figure 3B and Table 3).…”
Section: Discussionmentioning
confidence: 96%
“…Thus, observations from clinical studies [24,25,29] and the data in this study suggest a causal role for smoking-related free radicals in lung carcinogenesis. Very few studies have considered sex in the assessment of chemically induced oxidative DNA damage [64]. In a study of benzeneexposed workers, Liu et al [65] found signi®cantly higher levels of 8-oxo-dG in lymphocyte DNA in women versus men, however, no gender-dependent differences in oxidative DNA damage was observed between controls.…”
Section: Discussionmentioning
confidence: 98%
“…The significant increase of 8-OHdG level in mitochondrial DNA of diabetic heart ( Figure 6) indicated the oxidative damage of DNA leading to diabetic cardiomyopathy. This is where 8-OH-dG can be considered as a promutagenic lesion in DNA that is generated in response to a number of chemicals that induce oxidative stress [33] and it is widely used as a marker of oxidative injury [34].…”
Section: Resultsmentioning
confidence: 99%